2011
DOI: 10.1002/elps.201100403
|View full text |Cite
|
Sign up to set email alerts
|

PDMS microchip coated with polydopamine/gold nanoparticles hybrid for efficient electrophoresis separation of amino acids

Abstract: In this paper, a novel, simple, economical and environmentally friendly method based on in situ chemically induced synthesis strategy was designed and developed for the modification of a poly(dimethylsiloxane) (PDMS) microchip channel with polydopamine/gold nanoparticles (PDA/Au NPs) to create a hydrophilic and biofouling resistant surface. Dopamine as a reductant and a monomer, and HAuCl(4) as an oxidant to trigger dopamine polymerization and the source of metallic nanoparticles, were filled into the PDMS mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 57 publications
0
35
0
Order By: Relevance
“…PDMS microchip with a simple cross‐configuration was fabricated as previously described procedure . Briefly, PDMS oligomer and curing agent were thoroughly mixed at a ratio of 10:1 w/w, degassed, and then poured on the SU‐8 2035 photoresist molding.…”
Section: Methodsmentioning
confidence: 99%
“…PDMS microchip with a simple cross‐configuration was fabricated as previously described procedure . Briefly, PDMS oligomer and curing agent were thoroughly mixed at a ratio of 10:1 w/w, degassed, and then poured on the SU‐8 2035 photoresist molding.…”
Section: Methodsmentioning
confidence: 99%
“…(B) Separation mechanism of the electrophoretic microchip system for five amino acids analysis integrated with end‐channel electrochemical detection. Reprinted with permission from …”
Section: Applications Of Pda In Cementioning
confidence: 99%
“…The formed polydopamine contains a large number of bioactive groups including catechol moieties, -OH and -NH 2 and therefore can bind strongly to different kinds of materials 14,17,18 . It has been found that the formed polydopamine nanolayer on the surface of many materials, such as noble metals, oxides, semiconductors and various synthetic polymers could improve the apatitemineralization ability and cell attachments [19][20][21][22][23] DAPI solution (5 mg mL -1 ) was added to counterstain the cell nuclei.…”
Section: Article Nanoscalementioning
confidence: 99%